Plan estratégico de marketing para la cooperativa de ahorro y crédito “Minga” Ltda. de ciudad de Riobamba - Guaminga Anilema, Julio Manuel (2015)
The strategic marketing plan which arises following general aims, ensure that the Savings and Credit Cooperative (COAC) Minga Ltda, implement a branch in the city of Alausí according to the variables and indicators developed segmentation market and on the basis of the available financial resources. For the development of this research was based on a analysis of the current situation of the COAC "Minga" LTDA, then proceeded to make the macro and micro environment based on PEST analysis and Porter's 5 Forces, obtaining a factor weighting of 3.0, indicating that the opportunities outweigh the threats; then internal analysis of the Cooperative, helped with technical surveys and interviews, reaching to identify strengths and weaknesses of the Cooperative and obtaining a weighting factor of 2.88, indicating that the strengths outweigh the weaknesses was performed. The four elements of SWOT analysis, we proceeded to cross the four variables in order to find strategic objectives through the FO, DO, FA, DA Analysis, which are: • Improve the positioning of the COAC "Minga" LTDA sector. • Creation of the Department of Marketing and implementation of a Plan of Promotion and Advertising. • Improve customer service by improving response times credits. • Develop institutional arrangements. The implementation and development of these strategic objectives will have a total cost of $ 50,840.00 USD, it is recommended to comply with and implement the proposed strategies present in the project to achieve the positioning of the COAC Minga Ltda Strategic Marketing Plan along with financial products that bid